A thrifty variant in CREBRF strongly influences body mass index in Samoans - Minster, Ryan L; Hawley, Nicola L; Su, Chi-Ting; Sun, Guangyun; Kershaw, Erin E; Cheng, Hong; Buhule, Olive D; Lin, Jerome; Reupena, Muagututi'a Sefuiva; Viali, Satupa'itea; Tuitele, John; Naseri, Take; et al. (Nature genetics, 2016)
Stephen McGarvey and colleagues identify a missense variant in CREBRF strongly associated with body mass index in Samoans. This variant is rare in other populations but is common in Samoans and has a much larger effect size than other known common obesity risk variants, including variation in FTO . Samoans are a unique founder population with a high prevalence of obesity 1 , 2 , 3 , making them well suited for identifying new genetic contributors to obesity 4 . We conducted a genome-wide association study (GWAS) in 3,072 Samoans, discovered a variant, rs12513649, strongly associated with body mass index (BMI) ( P = 5.3 × 10 −14 ), and replicated the association in 2,102 additional Samoans ( P = 1.2 × 10 −9 ). Targeted sequencing identified a strongly associated missense variant, rs373863828 (p.Arg457Gln), in CREBRF (meta P = 1.4 × 10 −20 ). Although this variant is extremely rare in other populations, it is common in Samoans (frequency of 0.259), with an effect size much larger than that of any other known common BMI risk variant (1.36–1.45 kg/m 2 per copy of the risk-associated allele). In comparison to wild-type CREBRF, the Arg457Gln variant when overexpressed selectively decreased energy use and increased fat storage in an adipocyte cell model. These data, in combination with evidence of positive selection of the allele encoding p.Arg457Gln, support a 'thrifty' variant hypothesis as a factor in human obesity.